10 times 10 - Tullet, Hervé (Tate Publishing, 2014)
How many ways can you count to 10? With numbers, fingers, paints? How about with racing cars or with a fairy tale? In fact, you can do it almost any way you like! Herve Tullet, who has established an international reputation for creating dynamic books for young children, brings us this smart and silly counting book that will teach and entertain in equal measure. Counting has never been so much fun!